PENGARUH LATIHAN DUMBBELL FLY TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA TIM TENIS LAPANGAN PELTI DUMAI - Mahmudda Alfasya; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to know the effect of dumbbell fly practice effect arms and shoulders muscle at Pelti Dumai tennis team, so that when the athletes did dumbbell fly practice they have good arms and shoulders muscle.The problem is that the arms and shoulders muscle strength of Pelti Dumai tennis team still not enough, it’s seen from trials and frendly match nor formal and it’s one of the losing factor. The type of this research experiment, that’s to knowing the practice effect. This research purpose is to know the effect of dumbbell fly prectice to arms and shoulders muscle at Pelti Dumai tennis team.Population in this research are 6 Pelti Dumai tennis player the sample taking technique is all of thean used as sample data taking technigue is through pre test and post test. The instrument in this research is using strength test that is expanding dynamometer as the tool to measure arms and shoulders muscle strength.The analysis performed with t-test. Based on the data analysis, proved that 7,82 tcount and ttabel 1,943. So that tcount>ttabel. At some level ɑ=0,05. The conclusion is there is a significant effect from dumbbell fly practice to arms and shoulders at Pelti Dumai tennis team.Keyword : Dumbbell fly, arms and shoulders muscle strength , field tennis